Pengaruh CAR ( Capital Adequacy Ratio ), NPL (Non Performing Loan ), ROA (Return On Asset ), Dan BOPO ( Biaya Operasional Pendapatan Operasional ) Terhadap Penyaluran Kredit Pada Bank Umum Yang Terdaftar Di Otoritas Jasa Keuangan Periode 2016-2021 - Rizki Zumarnis; Moch Irsad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The banking industry is a crucial component of a nation's economic growth. Banking also performs the function of an intermediary institution, collecting monies from the community and redistributing them in the form of credit. Internal considerations that must be taken into account while channeling credit include those related to capital (proxied by CAR), koliektibilitas (proxied by NPL), profitability (proxied by ROA), measuring efficiency ( proxied BOPO). The research intends to examine the relationship between credit banking listed on the Indonesia Stock Exchange and the Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Return On Assets (ROA), and Operational Efficiency Ratio (BOPO). The subjects of this study were financial institutions registered with OJK between 2016 and 2021. The research sample consisted of 86 banking institutions. Multiple linear regression analysis is the method used in this research. Based on the analysis completed, it was determined that the ratio of CAR and ROA has a considerable favorable impact on the distribution of banking credit. The distribution of banking credit was significantly impacted negatively by the NPL percentage. While the distribution of banking credit is unaffected by the BOPO ratio. Keywords : Capital Adequacy Ratio, Non Performing Loan, Return On Assets, Operational Efficiency Ratio, Credit Distribution